Selective flotation of lepidolite from albite and quartz using a Hyperbranched surfactant THQ-8: Insights through foam property and adsorption behavior - Yukun Wu; Lingfeng Shen; Rui Xu; Ning Sun; Li Wang (Minerals Engineering, 2026)

Wearable triboelectric sensor based on a single-line-contact electrode architecture for gesture recognition and human–machine interaction - Long Li; Jingyun Dai; Jiayang Lyu; Yifan Shen; Yanmin Guo; Lingfeng Du; Zhiqian Wei; Xiongtu Zhou; Yongai Zhang; Hyung-Soon Kim; Dianlun Li; Kun Wang; et al. (Chemical Engineering Journal, 2026)

Flotation of quartz from albite using oligomeric surfactant THQ-8 in synergy with NaOL - Yukun Wu; Lingfeng Shen; Rui Xu; Ning Sun; Li Wang (Minerals Engineering, 2026)

Integrating machine learning and deep learning with multiple molecular fingerprints for topoisomerase I inhibitor screening and lead identification - Huang Zeng; Xuerou Zheng; Jiayao Liu; Shengyuan Zhang; Hua Nie; Nan Wang; Lingfeng Wu; Chunfang Liu; Ming Zhai; Hao Yang; Jiunlong Yang; Bo Qiu (Molecular Diversity, 2026)

Nonclassical modes of subtropical Indian Ocean dipole identified by autoencoder and their distinct climatic impacts - Bicheng Huang; Lingfeng Zheng; Zengping Zhang; Tao Su; Guolin Feng; Zhonghua Qian; Yongping Wu (Climate Dynamics, 2026)

Mechanisms of interlayer force transmission and slip surface penetration in pile-reinforced reservoir landslides with multi-sliding zones - Haojie Duan; Zongxing Zou; Yang Zhang; Lingfeng Wu; Jiang Li; Jianqiang Tao; Yikai Niu; Xinli Hu (Landslides, 2026)

Nutrient-acquisition and -utilization strategies of seagrasses in oligotrophic environments - Lin Wu; Jianguo Du; Lingfeng Huang; Hongtao Zhong (Frontiers in Marine Science, 2026)
Seagrass meadows rank among the most productive coastal ecosystems, yet our understanding of their nutrient-acquisition strategies in oligotrophic environments remain fragmented. Current research tends to focus on isolated processes, such as leaf or root uptake, without adequately integrating morpho-physiological traits, sediment heterogeneity, or microbial interactions. This fragmentation constrains our ability to predict seagrass responses to global environmental change. This review synthesizes seagrass nutritional ecology and shows that species in oligotrophic systems employ complementary strategies, including high-affinity foliar absorption, extensive root proliferation, and internal resorption. Crucially, these traits exhibit high plasticity and are modulated by intricate plant-microbe mutualisms, such as nitrogen fixation and phosphorus solubilization. We further demonstrate how sediment properties and hydrodynamic create spatial heterogeneity that dictates site-specific nutrient bioavailability. We propose three priority research directions: (1) deciphering the genetic and epigenetic drivers of phenotypic plasticity adaptation to oligotrophy; (2) applying stable isotope tracers and comparative genomics to quantify the net functional benefits of the seagrass microbiome; and (3) assessing long-term impacts of synergistic stressors (e.g., warming and eutrophication) on meadow structure and biogeochemical functions. By treating oligotrophic environments as natural laboratories, this review informs restoration efforts and the need to safeguard ecosystem services globally, particularly blue carbon sequestration and biodiversity conservation.

HMGB1 blockade attenuates cardiac injury induced by radiotherapy combined with PD-1 inhibitor while maintaining the anti-tumor efficacy - Yao Liu; Lingfeng Liu; Bibo Wu; Jing Zhang; Chaofen Zhao; Bing Lu; Yinxiang Hu; Weiwei Ouyang; Zhenneng Guo; Rong Hu; Shengfa Su (Apoptosis, 2026)

Leaf Size Variation in Response to Climate Drivers Depends on Plant Life Form - Jiayi Lu; Shihao Wen; Siyu Chen; Yuran Dong; Xiuping Wu; Yao Li; Min Zhang; Zhiwei Ge; Jonathan M. Chase; Lingfeng Mao (Journal of Biogeography, 2026)
Aim Plant leaf size and shape vary across major climatic gradients, reflecting the mechanisms for how plants regulate the balance of carbon, water, and heat. However, the influence of climate on leaf traits can be confounded by multiple factors, and the complex variation among different plant groups remains insufficiently understood. Here, we investigated how climate influences leaf size traits and whether this effect is moderated by plant life form. Location China. Taxon Angiosperms. Methods Based on leaf length, width, and aspect ratio data from 26,726 angiosperm species distributed across major climate gradients in China, we analysed the effects of temperature and precipitation on leaf size traits, and compared differences among plant life forms (woody vs. herbaceous and evergreen vs. deciduous). Additionally, spatial heterogeneity was assessed across eight vegetation zones. Results Leaves are generally larger and rounder in warm and humid areas, and smaller and narrower in cooler and more arid areas. All leaf size traits respond more strongly to precipitation than temperature, with leaf length showing the strongest responses to both climate variables. Herbaceous and deciduous species exhibit stronger climate responses nationwide, whereas woody and evergreen species are more sensitive within vegetation zones. Key responsive traits show clear geographic shifts. Main Conclusions Overall, we find that leaf size and shape vary strongly across China, as a result of climate variation, but these patterns are modified by dominant regional ecological processes and the ecological strategies of plant life forms. These findings not only help clarify variation in plant traits along climatic gradients, but also provide a theoretical framework for predicting how different plant morphologies will respond to ongoing climate change.

Fibre–emulsifier interactions shape the lipid digestion behaviour of high internal phase emulsions - Yifeng Lu; Lingfeng Wu; Aprilia Nur Khasanah; Maarten Schutyser; Lu Zhang; Karin Schroën; Meinou Corstens (Food Hydrocolloids, 2026)

Parallel cooperative path following control for multiple cyber-physical MASSs based on DN-ESO - Lingfeng Li; Lu Liu; Bing Han; Bing Wu; Zhouhua Peng (Ocean Engineering, 2026)

Effects of cold plasma treatment and xanthan gum on the longan seed starch: physicochemical, rheological and digestive properties - Rui Huang; Yitong Chen; Lingfeng Cheng; Mengzhu Shen; Yaqin Yu; Fangfang Wu; Miaomiao Shi; Yong Hu; Chao Huang; Yun Chen (Food Chemistry, 2025)

Sulfur vacancy-rich ZnIn2S4 via solvent engineering: Unveiling structure-defect-activity relationships for photocatalytic ranitidine degradation - Yilan Wang; Lingfeng Ouyang; Shuai Zhang; Zhanghong Zhou; Carolina Belver; Season Si Chen; Hao Wu (Chemical Engineering Journal, 2025)

Nanomaterial-powered immunotherapy: A next-generation therapeutic paradigm for bacterial infections - Xiaotong Sun; Shengnan Huang; Tong Ye; Lingfeng Xu; Yongfang Wang; Anqi Liu; Chao Liu; Yu Han; Mengfei Pang; Xuan Wu; Xin Pang (Chemical Engineering Journal, 2025)

Comparative analysis of machine learning based dissolved oxygen predictions in the Yellow River Basin: The role of diverse environmental predictors - Lingling Liu; Xiaoli Zhao; Lingfeng Zhou; Jiangtao Liu; Wenjing Li; Bolun Zhang; Junhong Ling; Fengchang Wu (Journal of Environmental Management, 2025)

Ultrasensitive SERS detection of cytokines through specific binding and multiple reporter molecules - Hairong Chen; Hengchang Zhang; Lingfeng Duan; Kaidi Sun; Rui Li; Yunxia Wang; Jiacheng Yao; Changchun Yan; Ying Liu; Ying Wu; Guohai Yang; Caiqin Han (Analytica Chimica Acta, 2025)

Propagation characteristics of meteorological drought to hydrological drought in China - Ding Luo; Xiaoli Yang; Lingfeng Xie; Zhoubing Ye; Liliang Ren; Linyan Zhang; Fan Wu; Donglai Jiao (Journal of Hydrology, 2025)

Effect of annealing and tea polyphenols on the physicochemical properties of mango starch - Rui Huang; Yaqin Yu; Mengzhu Shen; Lingfeng Cheng; Yitong Chen; Hongwei Wu; Fangfang Wu; Chao Huang; Yong Hu; Yun Chen (Food Bioscience, 2025)

High-throughput screening and inhibition mechanism analysis of Bacillus licheniformis BL-4 as an antagonistic strain for Lactobacillus panis - Lingfeng Yi; Xinyue Li; Menglin She; Yaokang Wu; Jianghua Li; Guocheng Du; Long Liu; Li Wang; Yanfeng Liu (Systems Microbiology and Biomanufacturing, 2025)

Surface passivated 3D halide perovskite single crystal by 2D perovskite towards high performance soft X-ray detection and gamma-ray spectrum - Yan Xiong; Min Li; Shunsheng Yuan; Yuting Liu; Tong Jin; Jincong Pang; Sihao Xia; Mingquan Liao; Lingling Liu; Lingfeng Wu; Kuan Yew Cheong; Huayang Yu; et al. (Chemical Engineering Journal, 2025)

Oral pH-Sensitive Solid Self-Microemulsion of Norcantharidin Wrapped in Colon-Coated Capsule for Selective Therapy of Colorectal Carcinoma - Xia Liu; Wenyou Fang; Wenjie Lu; Mingchao Xu; Zijun Wu; Dan Su; Lingzhen Ding; Qing Zhang; Jinguang Ouyang; Tianming Wang; Lingfeng Sun; Song Gao; et al. (AAPS PharmSciTech, 2025)

Causes of Atypical Meiyu in the Lower Yangtze River Basin in 2022: Subseasonal Perspective and Predictions - Zhiqi Zhang; Ping Liang; Yajing Liu; Yang Wu; Lingfeng Tao; Qi Chen; Yihui Ding (Journal of Meteorological Research, 2025)

A unimodal soil-water characteristic curve model for gap-graded soil based on bimodal grain-size distribution and fractal theory - Yuefeng Wu; Junsheng Chen; Weidong Pan; Lingfeng Guo; Yi Shan (Transportation Geotechnics, 2025)

Abrupt enhanced Pacific warm water intrusion into the Sea of Okhotsk since the early Holocene - Xuguang Feng; Jianjun Zou; Xuefa Shi; Zhengquan Yao; Zhi Dong; Jiang Dong; Yonghua Wu; Ruxi Dou; Hualong Jin; Aimei Zhu; Xiaojing Wang; Qingchao Wang; et al. (Quaternary Science Reviews, 2024)

Co-grown novel S-scheme tubular P–UCN/S-TCN homojunction mediates photocatalysis-PMS activation synergistic system for efficient degradation of antibiotic - Ting Wu; Zhifeng Liu; Binbin Shao; Yuan Pan; Qingyun He; Xiansheng Zhang; Lingfeng Zhou; Yunze Wang; Teng Li; Sheng Liu (Chemosphere, 2024)

Bioorthogonal surface-edited exosomes for targeted multimodal imaging and synergic chemophototherapy of oral cancer - Yuxiao Wu; Xiaofeng Shan; Yuanjie Zhang; Wen Shi; Xingxing Zhu; Mengfan Yu; Shang Xie; Lingfeng Guo; Zhiqian Chen; Chuanling Zhang; Demin Zhou; Zhigang Cai (Chemical Engineering Journal, 2024)

Influence of corrosion on seismic performance of steel beam-to-column connections - Yuelin Zhang; Cheng Fang; Wei Wang; Lingfeng Wu; Peng Cao (Engineering Structures, 2024)

Effect of propranolol on pharmacokinetics of clozapine in schizophrenic patients: a meta-analysis - Xiding Yang; Qiangyong Yan; Lingfeng Yang; Jingjing Li; Xiao Fan; Jindong Chen; Haishan Wu; Yongyu Yang; Ronghua Zhu; Pingfei Fang (European Journal of Clinical Pharmacology, 2024)

Potential high-risk release sources of thallium and arsenic from surrounding rocks of a typical thallium and arsenic mining area in southwest China - Yanpei Du; Lingfeng Shi; Xinyan Cao; Fengqi Zhao; Pengjie Hu; Rongrong Ying; Shangyi Gu; Longhua Wu; Yongming Luo; Peter Christie (Science of The Total Environment, 2024)

Structural stability and release properties of emulsion-alginate beads under gastrointestinal conditions - Lingfeng Wu; Karin Schroën; Meinou Corstens (Food Hydrocolloids, 2024)

Differences in the activities of six soil enzymes in response to cadmium contamination of paddy soils in high geological background areas - Juan Liu; Xinyang Li; Qilin Zhu; Jiawen Zhou; Lingfeng Shi; Weihong Lu; Li Bao; Lei Meng; Longhua Wu; Naiming Zhang; Peter Christie (Environmental Pollution, 2024)

Responses of microeukaryotic community structure to a Phaeocystis globosa bloom in a semi-enclosed subtropical bay - Beibei Han; Rongjun Shi; Shufei Zhang; Anji Lian; Zexing Kuang; Fengxia Wu; Lingfeng Huang; Honghui Huang (Marine Environmental Research, 2024)

Potential mobilization of water-dispersible colloidal thallium and arsenic in contaminated soils and sediments in mining areas of southwest China - Yanpei Du; Lingfeng Shi; Xinyang Li; Juan Liu; Rongrong Ying; Pengjie Hu; Longhua Wu; Peter Christie (Journal of Hazardous Materials, 2024)

Water-dispersible colloids facilitate the release of potentially toxic elements from contaminated soil under simulated long-term acid rain - Juan Liu; Lingfeng Shi; Yanpei Du; Xueting Luo; Pengjie Hu; Longhua Wu; Yongming Luo; Peter Christie (Science of The Total Environment, 2024)

Vapor-liquid equilibrium measurement for carbon dioxide (CO2)+propylene (R1270) binary mixture at temperatures from subcritical to supercritical - Zirui Wu; Rui Sun; Lingfeng Shi; Peng Hu; Hua Tian; Xuan Wang; Gequn Shu (International Journal of Refrigeration, 2024)

MOF derived MnFeOX supported on carbon cloth as electrochemical anode for peroxymonosulfate electro-activation and persistent organic pollutants degradation - Xiansheng Zhang; Yuan Pan; Yunze Wang; Ting Wu; Binbin Shao; Qingyun He; Lingfeng Zhou; Teng Li; Sheng Liu; Xinyi Huang; Zhifeng Liu (Chemical Engineering Journal, 2024)

Application of 3D hierarchical porous NiCo-spinel nanosheet array for enhancement of synergistic activation of peroxymonosulfate: Degradation, Intermediates, mechanism and degradation pathway of tetracycline - Yuan Pan; Xiansheng Zhang; Ting Wu; Binbin Shao; Teng Li; Qingyun He; Zehua Chen; Lingfeng Zhou; Sheng Liu; Xinyi Huang; Zhifeng Liu (Chemical Engineering Journal, 2024)

An integrated analysis of the fecal metabolome and metagenome reveals the distinct effects of differentially charged nanoplastics on the gut microbiota-associated metabolites in mice - Miaomiao Teng; Xiaoli Zhao; Lingfeng Zhou; Hong Yan; Lihui Zhao; Jiaqi Sun; Yunxia Li; Wentao Zhu; Fengchang Wu (Science of The Total Environment, 2024)

Overlooked fluorine deficiency in children of South and East China may be exacerbated by climate change: Evidence from the national assessment - Lingfeng Zhou; Weigang Liang; Yaobin Meng; Xiaoli Zhao; Fei Guo; Lingling Liu; Wenjing Li; Miaomiao Teng; Fanhao Song; Zhiqiang Cao; Yidong Mi; Qigen Lin; et al. (Journal of Cleaner Production, 2024)

3D binder-free nanoarchitecture design of porous silicon/graphene fibers for ultrastable lithium storage - Yongbiao Mu; Ruijie Zhang; Bu-ke Wu; Ming Yang; Youqi Chu; Qing Zhang; Lingfeng Zou; Xianbin Wei; Zifan Liao; Haixiang Ren; Yiju Li; Lin Zeng (Chemical Engineering Journal, 2023)

Molecular docking and antibacterial activity of Sargassum fusiforme extracts against major coral pathogens - Nedaa Ahmed; Mohamed A. M. El-Tabakh; Hala F. Mohamed; Xudong Wu; Changan Xu; Lingfeng Huang (World Journal of Microbiology and Biotechnology, 2023)

Experimental studies on active oxygen control performance of solid PbO mass exchanger in liquid lead–bismuth eutectic loop - Ruixian Liang; Huiping Zhu; Zhenhua Sheng; Xiaobo Li; Muran Qi; Yifeng Wang; Lingfeng Yang; Xu Tu; Hao Wu; Fang Liu; Zhangpeng Guo; Haicai Lyu; et al. (Annals of Nuclear Energy, 2023)

Performance of potentiometric oxygen sensors with LSCF electrode in lead–bismuth eutectic loop - Ruixian Liang; Huiping Zhu; Lingfeng Yang; Muran Qi; Xiaobo Li; Yifeng Wang; Zhenhua Sheng; Xu Tu; Gaoxiang Xu; Boqing Li; Hao Wu; Haicai Lyu; et al. (Annals of Nuclear Energy, 2023)

Molecular-level insights into the heterogeneous variations and dynamic formation mechanism of leached dissolved organic matter during the photoaging of polystyrene microplastics - Fanhao Song; Tingting Li; Jin Hur; Quan Shi; Fengchang Wu; Wei He; Di Shi; Chen He; Lingfeng Zhou; Mingqi Ruan; Yuhan Cao (Water Research, 2023)

Construction of hybridization chain reaction induced optical signal directed change of photonic crystals-DNA hydrogel sensor and its visual determination for aflatoxin B1 - Qianshan Chen; Lingfeng Wu; Feng Zhao; Bing Liu; Zhaoyang Wu; Ruqin Yu (Food Chemistry, 2023)

Model-based evaluation of reduction strategies for point and nonpoint source Cd pollution in a large river system - Lingfeng Zhou; Xiaoli Zhao; Miaomiao Teng; Fengchang Wu; Yaobin Meng; Yating Wu; Patrick Byrne; Karim C. Abbaspour (Journal of Hydrology, 2023)

Modeling transport and fate of heavy metals at the watershed scale: State-of-the-art and future directions - Lingfeng Zhou; Fengchang Wu; Yaobin Meng; Patrick Byrne; Mory Ghomshei; Karim C. Abbaspour (Science of The Total Environment, 2023)

Integrated assessment of land-to-river Cd fluxes and riverine Cd loads using SWAT-HM to guide management strategies - Lingfeng Zhou; Miaomiao Teng; Fanhao Song; Xiaoli Zhao; Fengchang Wu; Yaobin Meng; Yuanyi Huang; Karim C. Abbaspour (Journal of Environmental Management, 2023)

Remediation of uranium-contaminated alkaline soil by rational application of phosphorus fertilizers: Effect and mechanism - Lingfeng Dong; Zhanfei He; Jingyi Wu; Keqing Zhang; Daoyong Zhang; Xiangliang Pan (Environmental Research, 2023)

A multicentre study on the incidence of respiratory viruses in children with community-acquired pneumonia requiring hospitalization in the setting of the zero-COVID policy in China - Ziheng Feng; Baoping Xu; Lili Zhong; Jing Chen; Jikui Deng; Zhengxiu Luo; Lingfeng Cao; Yu Tang; Changchong Li; Rong Jin; Li Deng; Yunxiao Shang; et al. (Archives of Virology, 2023)
Background Stringent nonpharmaceutical interventions (NPIs) have been implemented worldwide to combat the COVID-19 pandemic, and the circulation and seasonality of common respiratory viruses have subsequently changed. There have been few multicentre studies or comparisons of the prevalence of respiratory viruses accounting for community-acquired pneumonia (CAP) in hospitalized children between the pre-COVID period and the period after community and school reopening in the setting of the zero-COVID policy. Methods We included 1543 children with CAP who required hospitalization from November 1, 2020 to April 30, 2021 (period 1), and 629 children with the same conditions from November 1, 2018, to April 30, 2019 (period 2), in our study. All respiratory samples from these patients were screened for six respiratory viruses (respiratory syncytial virus [RSV], adenovirus [ADV], influenza A virus [Flu A], influenza B virus [Flu B], parainfluenza virus type 1 [PIV1], and parainfluenza virus type 3 [PIV3]) using a multiplex real-time PCR assay. Results and conclusions The median ages of the enrolled patients at the time of diagnosis were 1.5 years and 1.0 years for period 1 and period 2, respectively. In period 1, viral pathogens were detected in 50.3% (776/1543) of the enrolled patients. The most frequently identified viral pathogen was RSV (35.9%, 554/1543), followed by PIV3 (9.6%, 148/1543), PIV1 (3.6%, 56/1543), ADV (3.4%, 52/1543), Flu A (1.0%, 16/1543), and Flu B (0.8%, 13/1543). The total detection rates of these six viruses in the peak season of CAP were at the pre-COVID level. The prevalence of Flu A decreased dramatically, and circulation activity was low compared to pre-COVID levels, while the incidence of PIV3 increased significantly. There were no significant differences in the detection rates of RSV, ADV, Flu B, and PIV1 between the two periods. Our results showed that respiratory viruses accounted for CAP in hospitalized children at pre-COVID levels as communities and schools reopened within the zero-COVID policy, although the prevalence aetiology spectrum varied.

Combined toxicity of chlorpyrifos, abamectin, imidacloprid, and acetamiprid on earthworms (Eisenia fetida) - Miaomiao Teng; Xiaoli Zhao; Chen Wang; Lingfeng Zhou; Xiaowei Wu; Fengchang Wu (Environmental Science and Pollution Research, 2022)

Faster recovery of soil biodiversity in native species mixture than in Eucalyptus monoculture after 60 years afforestation in tropical degraded coastal terraces - Wenjia Wu; Luhui Kuang; Yue Li; Lingfeng He; Zhijian Mou; Faming Wang; Jing Zhang; Jun Wang; Zhi’an Li; Hans Lambers; Jordi Sardans; Josep Peñuelas; et al. (Global Change Biology, 2021)
Afforestation is an effective method to restore degraded land. Afforestation methods vary in their effects on ecosystem multifunctionality, but their effects on soil biodiversity have been largely overlooked. Here, we mapped the biodiversity and functioning of multiple soil organism groups resulting from diverse afforestation methods in tropical coastal terraces. Sixty years after afforestation from bare land (BL), plant species richness and the abundance of plant litter (398 ± 85 g m −2 ) and plant biomass (179 ± 3.7 t ha −1 ) in native tree species mixtures (MF) were restored to the level of native forests (NF; 287 ± 21 g m −2 and 243.0 ± 33 t ha −1 , respectively), while Eucalyptus monoculture (EP) only successfully restored the litter mass (388 ± 43 g m −2 ) to the level of NF. Soil fertility in EP and MF was increased but remained lower than in NF. For example, soil nitrogen and phosphorus concentrations in MF (1.2 ± 0.2 g kg −1 and 408 ± 49 mg kg −1 , respectively; p −1 and 523 ± 24 mg kg −1 , respectively; p

Study on bioleaching of heavy metals and resource potential from tannery yard sludge - Hang Liu; Kaizhi Yang; Lingfeng Luo; Qian Lu; Yonggui Wu; Meiyan Lan; Youfa Luo; Wan Liang (Environmental Science and Pollution Research, 2021)

Assessment of uranium migration and pollution sources in river sediments of the Ili River Basin using multiply statistical techniques - Lingfeng Dong; Zhanfei He; Fan Zhang; Tao Xu; Jingyi Wu; Kaifang Yan; Xiangliang Pan; Daoyong Zhang (Environmental Science and Pollution Research, 2021)

Enhanced abatement of organic contaminants by zero-valent copper and sulfite - Xiaodan Zhao; Ying Wu; Danying Xing; Zhaojin Ren; Lingfeng Ye (Environmental Chemistry Letters, 2020)

Performance of the BDS3 experimental satellite passive hydrogen maser - Ziqian Wu; Shanshi Zhou; Xiaogong Hu; Li Liu; Tao Shuai; Yonghui Xie; Chengpan Tang; Junyang Pan; Lingfeng Zhu; Zhiqiao Chang (GPS Solutions, 2018)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)